PERUBAHAN KARAKTERISTIK FISIKOKIMIA TEPUNG ONGGOK SELAMA PROSES FERMENTASI SEMI PADAT MENGGUNAKAN SACCHAROMYCES CEREVISIAE - Hidayat, Beni; Muslihudin, M.; Akmal, Syamsu (Jurnal Penelitian Pertanian Terapan, 2018)
Cassava bagasse is a by-product of tapioca industry whose use as food is relatively limited.The improvement of the cassava bagasse flour characteristics as a food ingredient can bedone through a semi-solid fermentation process. The aim of this study was to examine thechanges in physicochemical characteristics of cassava bagasse flour during the semi-solidfermentation process using Saccharomyces cerevisiae. The semi-solid fermentation processwas carried out for 0 days (control), 1 day, 2 days, 3 days, 4 days, and 5 days. Observationsof physicochemical characteristics include pasting characteristics, microstructure, waterabsorption index, and water solubility index. The results showed that the fermentationprocess had no effect on the gelatinization temperature but affected the viscosity of thecassava bagasse flour; during fermentation, liberation and erosion of the starch granule willbe more intense occur, as well as an increase in water absorption index and water solubilityindex.